2021
DOI: 10.5194/acp-2021-53
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ice nucleation ability of Ammonium Sulfate aerosol particles internally mixed with Secondary Organics

Abstract: Abstract. The abundance of aerosol particles and their ability to catalyze ice nucleation are key parameters to correctly understand and describe the aerosol indirect effect on the climate. Cirrus clouds strongly influence the Earth's radiative budget, but their effect is highly sensitive to their formation mechanism, which is still poorly understood. Sulfate and organics are among the most abundant aerosol components in the troposphere and have also been found in cirrus ice crystal residuals. Most of the stud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…They found that the critical S ice of compositionally-mixed particles fell between that of ammonium sulfate and α-pinenederived SOA. More recently, Bertozzi et al 92 have demonstrated that SOA coatings can both enhance and decrease the ice nucleation abilities of ammonium sulfate particles, depending on the composition and aging state of the SOA material.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the critical S ice of compositionally-mixed particles fell between that of ammonium sulfate and α-pinenederived SOA. More recently, Bertozzi et al 92 have demonstrated that SOA coatings can both enhance and decrease the ice nucleation abilities of ammonium sulfate particles, depending on the composition and aging state of the SOA material.…”
Section: Resultsmentioning
confidence: 99%
“…The first was a stationary instrument permanently installed at the AIDA facility, called INKA (Ice Nucleation Chamber of the Karlsruhe Institute of Technology) (DeMott et al., 2018; Schiebel, 2017; Wagner et al., 2020). The second was a mobile version of INKA, called mINKA, which was developed for experiments in the Cosmics Leaving Outdoor Droplets (CLOUD) chamber at CERN (Bertozzi, 2021; M. Wang et al., 2022), but was also available for this study. Both INKA and mINKA are CFDCs with vertical cylindrical geometry (Rogers, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…mINKA has shorter cylinder walls (85 cm) than INKA, but is operated without an evaporation section to maximize the residence time of the particles in the diffusion section where nucleation and growth of the ice crystals can take place. Further technical details and a thorough comparison of the performance of the two CFDCs for different types of aerosol particles are given in Bertozzi (2021). Both instruments were operated in the “humidity scan mode,” where the temperature experienced by the aerosol particles was kept constant and RH was increased from ice‐saturated to water‐saturated conditions at an average dS ice /dt rate of about 0.03 min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Heterogeneous ice formation by ice-nucleating particles (INPs) allows for the formation of cirrus clouds at lower humidity than required for ice formation by homogeneous freezing of solution droplets, which is determined by the water activity criterion (Koop et al, 2000). Typical cirrus cloud INPs are water-insoluble particles such as mineral dusts, fly ash, metallic particles (DeMott et al, 2003;Cziczo et al, 2013) or soot (Bond et al, 2013). Prompted by the realization that secondary organic aerosol (SOA) particles can exist in a highly viscous, (semi-)solid state (Zobrist et al, 2008;Virtanen et al, 2010), the possibility that SOA particles could act as INPs has been investigated in recent years (Möhler et al, 2008;Prenni et al, 2009;Wang et al, 2012;Ladino et al, 2014;Schill et al, 2014;Ignatius et al, 2016;Charnawskas et al, 2017;Wagner et al, 2017;Bertozzi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Typical cirrus cloud INPs are water-insoluble particles such as mineral dusts, fly ash, metallic particles (DeMott et al, 2003;Cziczo et al, 2013) or soot (Bond et al, 2013). Prompted by the realization that secondary organic aerosol (SOA) particles can exist in a highly viscous, (semi-)solid state (Zobrist et al, 2008;Virtanen et al, 2010), the possibility that SOA particles could act as INPs has been investigated in recent years (Möhler et al, 2008;Prenni et al, 2009;Wang et al, 2012;Ladino et al, 2014;Schill et al, 2014;Ignatius et al, 2016;Charnawskas et al, 2017;Wagner et al, 2017;Bertozzi et al, 2021). SOA acting as INPs affect precipitation formation, cloud cover and the cloud albedo.…”
Section: Introductionmentioning
confidence: 99%